Consequences of fractionally integrated regressors - Werner Ploberger (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1999)
This paper analyzes linear models. It investigates the difference between the sum of squares of the residuals and the sum of squares of the prediction errors when the parameter is estimated consecutively. In case the regressors are “fractionally integrated” (in a very broad sense) it is shown that the asymptotic behavior of this difference is determined by the order of integration of the regressors.
Keywords: 519